Extracting functional groups of ALLINI to design derivatives of FDA‐approved drugs: Inhibition of HIV‐1 integrase. (21st February 2018) - Kalathiya, Umesh; Padariya, Monikaben; Baginski, Maciej
Abstract: HIV‐1 integrase (IN) is crucial for integration of viral DNA into the host genome and a promising target in development of antiretroviral inhibitors. In this work, six new compounds were designed by linking the structures of two different class of HIV‐1 IN inhibitors (active site binders and allosteric IN inhibitors (ALLINIs)). Among newly designed compounds, INRAT10b was found most potent HIV‐1 IN inhibitor considering different docking results. To further validate protein–ligand interactions obtained from dockings, molecular dynamics simulations were performed for inhibitor raltegravir and INRAT10b placed either at active site or allosteric site of HIV‐1 IN (monomer or dimer). Results suggest that both raltegravir and INRAT10b were interacting with residue Gln62, Gly140, Ile141, and Ser147. However, INRAT10b interacts better with high H‐bond occupancy, which can explain the strong binding affinity of INRAT10b than raltegravir with the HIV‐1 IN protein. Subdomains rearrangements in HIV‐1 IN suggest that the C‐terminal and catalytic core domains develop their closeness in the presence of ligand. More significantly, the newly designed derivatives represent novel compounds targeting catalytic site and C‐terminal (protein–protein interaction) domains simultaneously. And we also propose INRAT10b as a promising lead compound for the development of potent HIV‐1 IN inhibitors.